Does it matter where you work? Employer characteristics and the wage growth of low-wage workers and higher-wage workers - Jens Stephani (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2013)
Using rich German linked employer-employee data and endogenous switching regression models, I show that large firms and firms with a high export share or a low proportion of fixed-term workers provide higher wage growth for low-wage workers. While having many low-paid co-workers dampens the wage growth of both lowwage workers and higher-wage workers, there are also employers who provide higher wage growth only for higher-wage workers. The results indicate a certain degree of labour market segmentation that is a) important for the wage mobility of individual workers and b) relevant in the context of polarisation and rising wage inequality. – – Unter Verwendung von umfangreichen verbundenen Arbeitgeber-Arbeitnehmer-Daten aus Deutschland und multivariaten Modellen mit 'endogenem Switching' wird in dieser Studie gezeigt, dass die Löhne von Geringverdienern in großen Betrieben und in Betrieben mit einer hohen Exportquote oder einem niedrigen Anteil befristet Beschäftigter vergleichsweise stärker wachsen als in anderen Betrieben. Ein hoher Anteil von Geringverdienern an der Belegschaft dämpft sowohl das Lohnwachstum von Geringverdienern als auch dasjenige von Höherverdienern. Außerdem zeigt sich, dass bestimmte Arbeitgeber nur Höherverdienern ein vergleichsweise erhöhtes Lohnwachstum bieten. Die Ergebnisse deuten auf eine gewisse Segmentation des deutschen Arbeitsmarktes hin. Letztere ist sowohl für die individuelle Lohnmobilität von Beschäftigten als auch im Kontext einer Polarisierung des Arbeitsmarktes und steigender Lohnungleichheit von Bedeutung.
Keywords: J30; J60; 330; Wage mobility; low-wage employment; endogenous switching regression model; Germany